2018
DOI: 10.1029/2017wr021681
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Syndepositional Macropores on the Hydraulic Integrity of Thick Alluvial Clay Aquitards

Abstract: Clay‐rich deposits are commonly assumed to be aquitards which act as natural hydraulic barriers due to their low hydraulic connectivity. Postdepositional weathering processes are known to increase the permeability of aquitards in the near surface but not impact on deeper parts of relatively thick formations. However, syndepositional processes affecting the hydraulic properties of aquitards have previously received little attention in the literature. Here, we analyze a 31 m deep sediment core recovered from an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…Further studies at this site include Acworth et al (2016) and Acworth et al (2017), which were precursors to Rau et al (2018) in the investigation of pore pressure response to atmospheric tides, and Timms et al (2018) on a core scale analysis of the site's laterally extensive and thick aquitard. Due to the sufficient M 2 response, time-series data of groundwater pressure heads measured between the 21/01/2016 and 14/04/2018 were used from the bore BH30061 which is located at latitude −31.518340 • , longitude 150.468332 • and an elevation of 313 MASL (WGS84).…”
Section: Cattle Lane (Nsw Australia)mentioning
confidence: 99%
“…Further studies at this site include Acworth et al (2016) and Acworth et al (2017), which were precursors to Rau et al (2018) in the investigation of pore pressure response to atmospheric tides, and Timms et al (2018) on a core scale analysis of the site's laterally extensive and thick aquitard. Due to the sufficient M 2 response, time-series data of groundwater pressure heads measured between the 21/01/2016 and 14/04/2018 were used from the bore BH30061 which is located at latitude −31.518340 • , longitude 150.468332 • and an elevation of 313 MASL (WGS84).…”
Section: Cattle Lane (Nsw Australia)mentioning
confidence: 99%
“…For example, it has been shown that structural heterogeneity can impact water infiltration in soils and the emergence of preferential flow [59], the development of unsaturated zones at the river-aquifer interface [58], and the distribution of saline and fresh water within the continental shelf [40]. The occurrence of structural heterogeneity, in the form of high permeability zones within aquitards, can also compromise their ability to act as barriers for water and contaminant migration [60]. In addition, the contrast in permeability between different geological layers may control the mechanisms for attenuation of CO 2 , when considering leakage from an underground reservoir used for carbon capture and storage [43,51,32].…”
Section: Environmental Relevance Of Structural Heterogeneitymentioning
confidence: 99%
“…For the sake of demonstration, we focus here on diffusion and sorption of groundwater contaminant in fully saturated clay. This process is relevant, for example, in clay liners of landfills (Hendry et al., 2003; Timms et al., 2018) or in long‐term tailing of groundwater pollution (Huang & Goltz, 2015; Johnson et al., 2003).…”
Section: Introductionmentioning
confidence: 99%